Answer:
B. 10C6(5y)^4(3)^6
Explanation:
The general binomial expansion formula is expressed using the formula:
(x+y)ⁿ = nCr x^{n-r}y^r
Given the equation (5y+3)^10
To get the sixth term of the expansion, we will compare the general formula given with the question
On comparison, x = 5y y = 3 and n = 10. Since we need the sixth term of the sequence, r will be equal to 6 i.e r = 6
Substitute the variables into the binomial formula above to get the sixth term.
(5y+3)^10 = 10C6 (5y)^10-6 (3)6
(5y+3)^10 = 10C6(5y)^4(3)^6
Hence the sixth term in the binomial expansion is 10C6(5y)^4(3)^6